Arthroscopic Treatment of Popliteus Tendinitis Using the Accessory Portal - Chen, B.; Liu, H. K.; Wang, H. (Frontiers in Surgery, 2022)
Introduction This study aimed to evaluate the effect of arthroscopic treatment of popliteus tendinitis via an auxiliary extreme lateral approach and to investigate the pathogenesis and treatment of popliteus tendinitis. Materials and Methods From 2016 to 2020, arthroscopic popliteus tendon ablation was performed in 15 patients (15 knees) with popliteus tendinitis via an auxiliary extreme lateral approach. Clinical outcomes were assessed using the Lysholm knee scoring scale, the Tegner score, the International Knee Documentation Committee (IKDC) score and the visual analogue scale (VAS) pain score at the 24-month follow-up after surgery. Results A total of 15 patients (mean age, 51.1 ± 7.1 years) were included. They had a mean body mass index of 23.8 ± 2.1 kg/m2. The minimum follow-up period was 24 months. Comparing the postoperative state to the preoperative state, the mean postoperative Lysholm score, Tegner score, and IKDC score improved significantly from 70.0 ± 5.0, 3.0 ± 0.9, and 62.3 ± 5.5 to 89.3 ± 4.2, 4.6 ± 0.61, and 80.5 ± 4.4, respectively (p < 0.01). The preoperative VAS score for pain improved from 6.4 ± 0.5 to 0.9 ± 0.4 (p < 0.01). No patients were lost to follow-up. Conclusions Following arthroscopic-assisted treatment, all the patients with popliteus tendinitis achieved satisfactory clinical outcomes in terms of pain relief and improved function. Level of Evidence Level IV